A 12-Week Cycling Workstation Intervention Improves Cardiometabolic Risk Factors in Healthy Inactive Office Workers. Issue 8 (11th August 2022) - Guirado, Terry; Metz, Lore; Pereira, Bruno; Brun, Carole; Birat, Anthony; Boscaro, Audrey; Bergouignan, Audrey; Thivel, David; Duclos, Martine
Abstract : Our research supports the evidence that using a portable pedal machine for 60 min per day enables to reduce cardiometabolic risk factors (waist-to-height ratio, us-CRP, total cholesterol and LDL-cholesterol) and improves weekdays movement behaviours in normal-weight healthy tertiary employees. Abstract : Objectives: The aim of this study was to evaluate the effects of a portable pedal machine intervention (60 minutes per working day) for 12 weeks on healthy tertiary employees' cardiometabolic risk factors. Methods: Anthropometric parameters, body composition, cardiometabolic/inflammatory markers, physical fitness, physical activity, and sedentary time measured before and after the intervention were compared between office healthy workers who used a portable pedal machine (INT, n = 17) and those who did not (CTRL, n = 15). Results: The INT group improved Δultrasensitive C-reactive protein ( P = 0.008), Δtotal cholesterol ( P = 0.028), and Δlight-density lipoprotein cholesterol ( P = 0.048) compared with the CTRL group (Δ: T1–T0). The intervention reduced daily sitting time ( P ≤ 0.01) and increased time spent at light intensity ( P ≤ 0.01) and moderate-to-vigorous ( P ≤ 0.01) physical activity compared with baseline values. Conclusions: These findings suggest that promoting physical activity during workdays can reduce the negative health effects of spending too much time sitting and inactive.